2023
DOI: 10.3390/polym15163400
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Strength and Sustainability: Evaluating Glass and Basalt Fiber-Reinforced Biopolyamide as Alternatives for Petroleum-Based Polyamide Composite

Dariusz Bednarowski,
Patrycja Bazan,
Stanisław Kuciel

Abstract: This study aims to analyze strength properties and low-cycle dynamic tests of composite materials modified with glass and basalt fibers. Biopolyamide 4.10 was used as the matrix, and the fiber contents were 15, 30, and 50% by weight. Static tensile tests, impact tests, and determination of mechanical hysteresis loops were carried out as strength tests. The length of the fibers in the produced composites and their processing properties were determined. The composite materials were compared with commercially ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The use of different compounding methods for basalt fiber composites, although necessary, was associated with undesirable effects. As described in the scientific literature, the average fiber length in the compound is significantly reduced with increasing dwell time in the extruder [21].…”
Section: Specimens Preparationmentioning
confidence: 69%
See 2 more Smart Citations
“…The use of different compounding methods for basalt fiber composites, although necessary, was associated with undesirable effects. As described in the scientific literature, the average fiber length in the compound is significantly reduced with increasing dwell time in the extruder [21].…”
Section: Specimens Preparationmentioning
confidence: 69%
“…Bednarowski et al investigated mechanical properties of composites with basalt and glass fibers [21]. Although the research concerned partially biobased PA 4.10 and not PA 10.10, the results proved the usefulness of basalt fibers as a replacement for glass fibers in PA composites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A critical review of literature suggests that glass fiber reinforcements provide good stiffness and high tensile strength 6 . Few studies also reported that Epoxy polymer matrix provides good stiffness, high strength and good corrosion resistance 7,8 .…”
mentioning
confidence: 99%